2017
DOI: 10.1002/jum.14343
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Validation of DXA‐Derived Appendicular Fat‐Free Adipose Tissue by a Single Ultrasound Image of the Forearm in Japanese Older Adults

Abstract: Our results indicated that a single ultrasound forearm measurement can be used to accurately estimate DXA-derived aLM-minus-FFAT in Japanese older adults, which may be advantageous for community-based physical examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Forearm musculature was evaluated at proximal 30% between the head of the radius and the styloid process of the ulna, in a standing position with the arm supinated, for muscle thickness [43].…”
Section: Lower Armmentioning
confidence: 99%
“…Forearm musculature was evaluated at proximal 30% between the head of the radius and the styloid process of the ulna, in a standing position with the arm supinated, for muscle thickness [43].…”
Section: Lower Armmentioning
confidence: 99%
“…However, the validity of this method on the individual level is limited [5]. Alternatively, ultrasound is used to estimate peripheral muscle size [6e9], and based on multiple peripheral muscle size measurements, to estimate total muscle mass [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although not reported within this paper, we previously noted that two of those prediction equations selected by Nijholt et al included systematic error . Over the last couple of years, we have published several prediction equations for estimating DXA‐derived appendicular lean mass in older adults . Unfortunately, those equations were not included in the article by Nijholt et al Interestingly, a single site measurement of forearm muscle thickness was found to be good predictor of DXA‐derived lean soft tissue mass in older Caucasian adults, and the equation was also found to be accurate in older Japanese adults .…”
mentioning
confidence: 78%
“…5 Over the last couple of years, we have published several prediction equations for estimating DXA-derived appendicular lean mass in older adults. [6][7][8] Unfortunately, those equations were not included in the article by Nijholt et al 4 Interestingly, a single site measurement of forearm muscle thickness was found to be good predictor of DXA-derived lean soft tissue mass in older Caucasian adults, 6 and the equation was also found to be accurate in older Japanese adults. 7 Notably, the standard error of the estimate was 1.95 kg for the equation that used a single muscle thickness site, whereas the standard error of the estimate of the equation that included eight predictors was 1.13 kg.…”
mentioning
confidence: 99%